1999
DOI: 10.1111/j.1600-0765.1999.tb02255.x
|View full text |Cite
|
Sign up to set email alerts
|

Protein recovery from several paper types used to collect gingival crevicular fluid

Abstract: The purpose of this study was to compare the efficiency of protein elution from several types of gingival crevicular fluid (GCF) collection papers when the volume of the inoculated protein and the elution methods were constant. Various concentrations of bovine serum albumin (BSA) and 14C-BSA were placed onto strips of Whatman #1 [W1], Whatman 3 MM chromatographic [W3], Periopaper (ProFlow) [P] and Periopaper (Harco) [H], and recovered proteins measured following a non-optimized centrifugal elution technique. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 61 publications
1
17
0
Order By: Relevance
“…[21] It has been previously reported that protein recovery rates from Periopaper points is not consistent, and depends on nature of the proteins and their concentrations. [22] But, we confirmed the reproducible evidence that protein recovery rates are relatively high and constant (80-87%) from Periopaper using IL-1b, b2-MG, and albumin in a preliminary way. b2-MG was determined by a sandwich ELISA that consisted of solid-phase (polystyrene bead)-immobilized antibodies and antibodies labeled with b-D-galactosidase, as described previously.…”
Section: Methodssupporting
confidence: 81%
“…[21] It has been previously reported that protein recovery rates from Periopaper points is not consistent, and depends on nature of the proteins and their concentrations. [22] But, we confirmed the reproducible evidence that protein recovery rates are relatively high and constant (80-87%) from Periopaper using IL-1b, b2-MG, and albumin in a preliminary way. b2-MG was determined by a sandwich ELISA that consisted of solid-phase (polystyrene bead)-immobilized antibodies and antibodies labeled with b-D-galactosidase, as described previously.…”
Section: Methodssupporting
confidence: 81%
“…This finding was supported by the in vitro analysis; the recovery rate of IL‐8 was much lower from endodontic paper points compared to paper strips. An earlier study 37 also reported an incomplete recovery of proteins from paper points supposedly because of binding of GCF proteins to the paper. The difference in elution of IL‐6 and IL‐8 was most likely due to difference in the structure, charge distribution, and hydrophobicity of these cytokines molecules.…”
Section: Discussionmentioning
confidence: 89%
“…Elevated MMP-8 levels and activation in AP GCF have been documented before by our and other groups Lee et al, 1995;Nomura et al, 1998;Chen et al, 2000), whereas Romanelli et al (1999) and Mancini et al (1999), analyzing mouthrinses or GCF diluted with tap-water , did not detect MMP-13 in GCF samples. It should be kept in mind that GCF sample collection methods and materials (Johnson et al, 1999) evidently affect the apparent levels and amounts of different MMPs (Ingman et al, 1996;Golub et al, 1997;Nomura et al, 1998;Mancini et al, 1999;Romanelli et al, 1999;Sorsa et al, 1999;Chen et al, 2000). The soluble pro-form of 58-kDa MT1-MMP or MMP-14 was demonstrated for the first time in human GCF.…”
Section: The Presence Of Mmps In Gcf Samplesmentioning
confidence: 99%